Development of nanogap automated permittivity measurement system for DNA hybridization detection kit - Saifullah, A.; Azri, M. E.; Uda, Hashim, Prof. Dr. (Institute of Electrical and Electronics Engineering (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/